(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article systematically and scientifically analyzes the role, significance, and limitations of the Central Asian factor in Turkey’s regional security policy. Within the framework of the study, the main directions of security cooperation between Turkey and the Central Asian states, institutional mechanisms, the geopolitical competitive environment, and transnational threats were examined from both theoretical and empirical perspectives. In addition, the cultural-diplomatic, geoeconomic, and military instruments employed by Turkey to strengthen its strategic influence in the region were analyzed. The findings demonstrate that Turkey’s security strategy in the region is being shaped within a competitive environment involving the Central Asian states pursuing multi-vector foreign policies, as well as major geopolitical actors such as Russia and China.